Water fetching and musculoskeletal health across the life-course in Sub-Saharan Africa: A scoping review. - Soren Meeuwisse; Susan J Elliott; Alexa Bennett; Videsh Kapoor (Public Library of Science (PLoS), 2024)
The world is experiencing a global water crisis and Sub-Saharan Africa (SSA) is expected to be a hotspot for increasing global water scarcity in years to come. Water is quintessentially a gendered issue; indeed, sociocultural norms hold women responsible for household water collection, requiring them to travel far distances while carrying water. This paper reports the findings of a scoping review of peer-reviewed and grey literature that examines the relationship between water fetching and the musculoskeletal (MSK) health of women in SSA. The work is informed by a gendered life-course perspective, and the authors follow the PRISMA-ScR guidelines. Results indicate a bidirectional relationship between water fetching and poor MSK health as chronic and acute incidences of water carrying are highly related to MSK pain and dysfunction. This has negative implications for the overall health and wellbeing of women and their households. Gaps in the literature are identified, including the experiences of elderly people and people with various vulnerabilities. Recommendations from the literature are compiled to outline potential avenues of future research and innovation to better support the MSK health of water fetchers in SSA.